Modeling ant foraging: A chemotaxis approach with pheromones and trail formation. (21st November 2015) - Amorim, Paulo
Abstract: We consider a continuous mathematical description of a population of ants and simulate numerically their foraging behavior using a system of partial differential equations of chemotaxis type. We show that this system accurately reproduces observed foraging behavior, especially spontaneous trail formation and efficient removal of food sources. We show through numerical experiments that trail formation is correlated with efficient food removal. Our results illustrate the emergence of trail formation from simple modeling principles. Abstract : Graphical abstract: Abstract : Highlights: We model ant foraging behavior with partial differential equations of chemotaxis type. Numerical simulations show spontaneous formation of foraging trails. Trail formation is correlated with increased food removal efficiency. Simulation of the whole foraging cycle. Emergence of trail formation from simple modeling principles.